Characteristics of Instant Steamed Sponge Cake Flour from Blending Purple Sweet Potato Flour (Ipomoea batatas var ayumurasaki), Mung Bean Flour ( (Vigna radiata) and Corn Flour ( Zea mays) - Rina Yenrina; Kurnia Harlina Dewi; Yumarnis Yumarnis (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2023)
This research aims to get the best formulation which liked by panelist by considering the chemical characteristics from blending of purple sweet potato flour, mung bean flour and corn flour. This research has done at laboratory of agricultural technology, Andalas University, Padang on October until November 2021. The research has used Completely Randomized Design with 5 treatment and 3 repitition. Anlysis of data use Analysis of Varian ( ANOVA), obvious difference result will be continued with Duncan’s New Multiple Range ( DMRT) at 5% obvious level. Some treatment are blending purple sweet potato flour, mung bean flour and corn flour they are A (40% : 60%), B ( 40% :50% : 10%), C (40%: 40% : 20%), D ( 40% : 30% : 20% and E ( 40% : 20% : 40%). The research result indicate that blending of purple sweet potato flour, mung bean flour and corn flour is obvious significantly influenced to some analysis of water, ash, fat, protein,carbohidrate,antioxidan activity, water activity, crude fiber instant steamed sponge cake flour.